2012
DOI: 10.1200/jco.2012.30.15_suppl.e13588
|View full text |Cite
|
Sign up to set email alerts
|

Circulating VEGF levels as a biomarker to clinical benefit to PTC299, the first inhibitor of VEGF synthesis.

Abstract: e13588 Background: Solid tumor growth is dependent on angiogenesis, a process mediated primarily by vascular endothelial growth factor (VEGF). Currently approved anti-angiogenic agents sequester VEGF or block activation of VEGF receptors. Despite extensive investigations, no reliable biomarkers have been identified for these agents. PTC299 is an investigational oral small molecule that differs from existing therapies by inhibiting VEGF synthesis at the translational level while conserving physiologic VEGF exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies in cancer patients at doses used in these studies demonstrated that PTC299 reduces levels of VEGF in cancer patients . Because the healthy subjects in these studies were not under physiological stress and based on the mode of activity of PTC299, as expected, we did not observe a PTC299‐induced pharmacodynamic effect on circulating VEGF.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Studies in cancer patients at doses used in these studies demonstrated that PTC299 reduces levels of VEGF in cancer patients . Because the healthy subjects in these studies were not under physiological stress and based on the mode of activity of PTC299, as expected, we did not observe a PTC299‐induced pharmacodynamic effect on circulating VEGF.…”
Section: Discussionmentioning
confidence: 67%
“…Studies in cancer patients at doses used in these studies demonstrated that PTC299 reduces levels of VEGF in cancer patients. [13][14][15][16] Because the healthy subjects in these studies were not under physiological stress and based on the mode of activity of PTC299, as expected, we did not observe a PTC299-induced pharmacodynamic effect on circulating VEGF. The phase 1 studies in healthy volunteers reported here provide an important understanding of the safety and pharmacokinetics of PTC299 and will allow us to model dosing and predict exposures more accurately if PTC299 goes forward in nononcological indications or for specific oncological indications.…”
Section: Discussionmentioning
confidence: 99%